2020
DOI: 10.30955/gnj.003387
|View full text |Cite
|
Sign up to set email alerts
|

Energy Demand and Carbon Emission Peak Forecasting of Beijing Based on Leap Energy Simulation Method

Abstract: <p>The long-term forecasting of the energy demand is an important issue of an area’s sustainable development, especially for mega cities such as Beijing. Beijing is changing its energy supply strategy to depend on energy imports from other provinces due to the city’s long-term low carbon sustainable development plan. Beijing has promised that it will reach the peak value of energy consumption by 2050 and the peak value of the carbon emissions by 2030. To understand whether this can be achieved, this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…The research revealed that, in the long run, the energy-saving strategy of the construction industry will be very important to Guangzhou [86]. Similarly, Wang J. et al (2020) predicted the energy demand and peak carbon emissions for Beijing and found that enhancing the energy efficiency of the tertiary industry and improving the industrial structure is an effective way to decrease energy use and carbon emissions [87].…”
Section: Author Co-citation Analysismentioning
confidence: 98%
“…The research revealed that, in the long run, the energy-saving strategy of the construction industry will be very important to Guangzhou [86]. Similarly, Wang J. et al (2020) predicted the energy demand and peak carbon emissions for Beijing and found that enhancing the energy efficiency of the tertiary industry and improving the industrial structure is an effective way to decrease energy use and carbon emissions [87].…”
Section: Author Co-citation Analysismentioning
confidence: 98%